Türkiye İktisat Tarihinde Öznel Boyutları ile Müdahaleciliğin Gelişimi ve Kurumsallaşması: Etibank Örneği - Doğangün Yasa, Bengü (Muş Alparslan Üniversitesi, 2019)
Thestate interventionism was tried to be arranged in an institutional framework inTurkish economic history from the early periods of the republic. This studyaims to find out the corporate facts of the state interventionism in Turkey byanalyzing activities of Etibank which was established for representing theinterventionism in the heavy industry area between 1935-1950 and legalregulations were made in those years. Analyzing Turkish political economy in aparticular time using an institution contributes to characterizeinterventionism. In this study Etibank’s activities were observed and it wasrevealed that Turkish state interventionism had pragmatic features.

Türkiyeiktisat tarihinde Cumhuriyetin erken dönemlerinden itibaren devletmüdahaleciliği kurumsal bir çerçeve içerisinde oluşturulmaya çalışılmıştır. Buçalışma müdahaleciliği ağır sanayi alanında temsil etmek üzere kurulanEtibank’ın 1935-1950 tarihleri arasındaki faaliyetlerini ve bu dönemdegerçekleştirilen yasal düzenlemeleri analiz ederek; Türkiye’de devletmüdahaleciliğinin kurumsal boyutlarını ortaya çıkarmayı amaçlamaktadır. Türkiyeiktisat tarihinin belirli bir döneminde oluşturulmaya çalışılan ekonomipolitiğin, kurumsal bir örnek üzerinden analizi, müdahaleciliğin niteliğinintanımlanmasına katkı sağlayacaktır. Çalışmada Etibank’ın kuruluş yıllarınıtakiben faaliyetleri genel çerçevede incelenmiş; Türkiye’de devletmüdahaleciliğinin pragmatik nitelikler sergilediği gözlenmiştir.
The Development and Institutionalization of Interventionism with Subjective Facts in Turkish Economic History: Etibank Model
anemon
Keywords: State Interventionism; Statism; Etibank; Devletçilik; Devlet Müdahaleciliği; Etibank